Urbanisation and household consumption in China - Molnar, Margit (OECD Economics Department Working Papers, 2017)
This paper focusses on the link between urbanisation and consumption behaviour in China. Urbanisation is defined here as rural people moving to cities to work and migrant workers in cities obtaining urban residential status, against the backdrop of government plans to settle 100 million rural dwellers into cities and grant urban residential status to another 100 million migrant workers who already reside in cities. Using household data of the China Family Panel Studies dataset, the paper investigates the impact of those residential status changes on household consumption. The results of the analysis suggest that moving up the residential ladder in this way will likely result in increased consumption by almost 30% for both groups of people and thus contribute to rebalancing of the economy. Higher incomes and longer times in education are important drivers of this process, while a greater number of children in the family discourages consumption. This Working Paper relates to the 2017 OECD Economic Survey of China (www.oecd.org/eco/surveys/economic-survey-china.htm)